1980
DOI: 10.1111/j.1365-2621.1980.tb00919.x
|View full text |Cite
|
Sign up to set email alerts
|

The prediction of water activity in aqueous solutions in connection with intermediate moisture foods IV. aW Prediction in aqueous non electrolyte solutions

Abstract: Sum ma ryA systematic survey was made of water activity reduction in single non electrolyte aqueous solutions together with an examination of the theoretical aspects of a, predictions. The prediction of a, in multicomponent aqueous solutions of non electrolytes as well as of mixed strong electrolyte-non electrolyte solutions was also studied.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
39
0
2

Year Published

1999
1999
2015
2015

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 125 publications
(41 citation statements)
references
References 13 publications
0
39
0
2
Order By: Relevance
“…On the contrary, the Norrish equation was successfully used also for higher molecular weight compounds. This equation is more accurate in predicting a w values over a wider range of solute concentrations [29]. In this study, it is shown that the combination of the Raoult's law with the Norrish equation accurately predicts the water activity development as a function of the polyol concentration in the water activity range of 0.6 to 0.8, and also at higher water activities.…”
Section: Water Activity Prediction Of Monomeric Polyol Water Systemsmentioning
confidence: 96%
See 3 more Smart Citations
“…On the contrary, the Norrish equation was successfully used also for higher molecular weight compounds. This equation is more accurate in predicting a w values over a wider range of solute concentrations [29]. In this study, it is shown that the combination of the Raoult's law with the Norrish equation accurately predicts the water activity development as a function of the polyol concentration in the water activity range of 0.6 to 0.8, and also at higher water activities.…”
Section: Water Activity Prediction Of Monomeric Polyol Water Systemsmentioning
confidence: 96%
“…The Norrish equation with modified k i values resulted in a good approximation of experimental a w values in aqueous sorbitol and glycerol solutions [12,29]. It has been proven to be a successful model for predicting a w values of multi-solute aqueous polyol solutions [16,31,32].…”
Section: Introductionmentioning
confidence: 93%
See 2 more Smart Citations
“…Donde a w es la actividad de agua del medio de cultivo, x w es la fracción molar del agua, x s es la fracción molar del soluto y k es la constante para el soluto, que en esta ecuación tomó los valores de 6,47 y 1,16 para sacarosa y glicerol respectivamente (Chirife et al, 1980). Ecuación de Favetto y Chirife:…”
Section: Preparación De Medios De Cultivounclassified